Hydrocarbon Movability Properties of Sandstone Reservoirs of Sapele Shallow Field, Niger Delta, Southern Nigeria - Airen, Osariere John; Mujakperuo, Bernard Jimevwo Ovonorene (Journal of Science Research and Reviews, 2025)
Sapele shallow field is a prolific oil field which forms the proximal portion of Sapele field in the Niger Delta oil province, Nigeria. The Sapele field itself is an onshore field of OML 41 located in the North-western part (Greater Ughelli deposit) of the Niger Delta oil province. The Greater Ughelli deposit is characterized by paralic interbedded sandstone and shale with a thickness of over 3000 m. Well logs from six wells, well 21, well 22, well 29, well 30, well 31 and well 32 were integrated to study the hydrocarbon movability potential of the field. The hydrocarbon movability potential of the field was delineated by looking at the various hydrocarbon movability factors such as the flushed zone obtained from water saturation parameter, movable oil saturation which is arrived at by subtracting water saturation from flushed zone, residual oil saturation evaluated from the difference between hydrocarbon saturation and movable oil saturation, and hydrocarbon movability index which is the ratio of water saturation and flushed zone. The study area on an average has flushed zone water saturation () of 0.88, an average hydrocarbon saturation of 0.47, an average movable hydrocarbon saturation of 0.35, residual hydrocarbon saturation of 0.12 and an average movable hydrocarbon index of 0.6. This study has shown that Sapele shallow field just like Sapele deep field is very viable with good hydrocarbon storage and transmission ability.
Keywords: Sandstone; Hydrocarbon movability; Prolific; Interbedded; Water saturation